The Level of Awareness of Rural Woman in the Field of Home Health In Jam root Village in the Zummar Region/ Nineveh Province and Its Relationship with Some Variables - Madhas, Abdel-Aziz Hamid; Dawood, Maher Ibrahim (Diyala Agricultural Sciences Journal, 2021)
The research aims to identify the level of awareness of rural women in field health of the homestead in each field of study fields, the health of kids, the health of animals, and health of commons in Zummar region/ Nineveh Province, identify the correlation between awareness of rural women and variables of study age, the educational level, job of husband, number of family and number of kids in the field of health in Zummar region/ Nineveh Province, the research includes all the rural women in research region whose their number 115 respondents, were taken random samples from 20 respondents pre-test its excluded from the original sample, it became final study sample of 95 respondents, the data was collected from the study respondents by a questionnaire, that is consisted of two parts: the first part includes the personal variables, the second part included the dependent variable that is rural women awareness, it consists of 29 items. Statistical program -Spss- used in the analysis of the data, the results shows, that the level of general rural women awareness /in Jamroot village, in the Zummar region was low. There are significant relationships between the level of general rural women awareness and some of the studied variables. The researcher gives some conclusions, generally, weak of awareness of rural women, in Jamroot village, in Zummar region in the field of the home health and he recommends increase their knowledge and information through providing themselves with health bulletins of the animal's health, children health, and even adults health.